Biomimetic microsensors inspired by marine life - Kottapalli, Ajay Giri Prakash (Springer, 2016)
This book narrates the development of various biomimetic microelectromechanical systems (MEMS) sensors, such as pressure, flow, acceleration, chemical, and tactile sensors, that are inspired by sensing phenomenon that exist in marine life. The research described in this book is multi-faceted and combines the expertise and understanding from diverse fields, including biomimetics, microfabrication, sensor engineering, MEMS design, nanotechnology, and material science. A series of chapters examine the design and fabrication of MEMS sensors that function on piezoresistive, piezoelectric, strain gauge, and chemical sensing principles. By translating nature-based engineering solutions to artificial manmade technology, we could find innovative solutions to critical problems.
Keywords: Detectors.; Microelectromechanical systems.; Biomimicry.; Marine habitats.; elektronické knihy; electronic books